Preparing Students for Successful Online Intercultural Communication and Collaboration in Virtual Exchange - Fernández Gutiérrez, Begoña; Reljanovic Glimäng, Malin; Sauro, Shannon; O'Dowd, Robert (Journal of International Students, 2022)
In the context of Virtual Exchange (VE) it is often assumed that participants will be naturally prepared to interact online successfully with their international partners. However, there is ample evidence in the literature to suggest that VE participants are usually unaware of effective communicative strategies in synchronous and asynchronous online communicative contexts. Through action research, this article investigates how teachers can provide scaffolding for both these communicative modalities in online intercultural environments. It reports on a qualitative content analysis of conversational and self-reported data from a corpus of three VEs that were collected and triangulated in order to identify when, in what areas, and in what ways students could benefit from pedagogical mentoring. The article then presents key mentoring stages and strategies that were identified and provides insight into the type of scaffolding that VE teachers can provide their students to help them achieve successful (a)synchronous online intercultural interaction.